2013
DOI: 10.1108/rbf-05-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Why do firms cross‐list their shares on foreign exchanges? A review of cross‐listing theories and empirical evidence

Abstract: PurposeFinancial markets’ integration and technological advances in equity trading may have reduced the potential benefits from listing a firm's shares on a foreign exchange. Nevertheless, a significant number of firms continue to cross‐list every year. This paper examines the recent cross‐listing trends and reviews the literature on motives to cross‐list.Design/methodology/approachThe literature review includes a summary of theoretical studies grouped into cross‐listing theories including market segmentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 138 publications
(201 reference statements)
1
23
0
Order By: Relevance
“…It advances our understanding of the strategic interaction between cross-listed firms and their rivals, with respective capital structures, by proposing and testing a dyadic model that applies signaling theory, complemented by other information-based theories, in cross-listing. In a sense, the main motive of cross-listing shares in foreign exchanges is to reduce information asymmetry and improve a stock’s information environment (Charitou and Louca, 2009; Dodd, 2013). In our model, announcements of cross-listing are regarded as the sending of signals and analyzed from the viewpoint of the signaler.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It advances our understanding of the strategic interaction between cross-listed firms and their rivals, with respective capital structures, by proposing and testing a dyadic model that applies signaling theory, complemented by other information-based theories, in cross-listing. In a sense, the main motive of cross-listing shares in foreign exchanges is to reduce information asymmetry and improve a stock’s information environment (Charitou and Louca, 2009; Dodd, 2013). In our model, announcements of cross-listing are regarded as the sending of signals and analyzed from the viewpoint of the signaler.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…Firms cross-list their shares on foreign exchanges to enhance firm value, mainly through enhanced operational and financial performance (Charitou and Louca, 2009; Dodd, 2013). The value of cross-listing in more prestigious markets, for example, the United States, can be identified as the positive effect of stock price reactions in the home market, which is relatively smaller and less stringent (O’Conner, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand,Shen et al (2010) found that there was a cross-listing premium. Resolving the issue is beyond the scope of this chapter.3 See generallyDodd (2013).…”
mentioning
confidence: 99%